Orchard biomass residues: Chemical composition, biological activity and wood characterization of apricot tree (Prunus armeniaca L.). (5th January 2021) - Bruno, Maria Roberta; Russo, Daniela; Faraone, Immacolata; D'Auria, Maurizio; Milella, Luigi; Todaro, Luigi
Abstract: Recent EU directives have encouraged member states to follow circular economy guidelines on waste reuse, especially for waste originating from wood agro‐forest biomass. Delineating the antioxidant and chemical activity of biomass is a starting point to find new ways to utilize such materials. Here, an 8‐year‐old apricot ( Prunus armeniaca L.) tree stand located in southern Italy was evaluated. First, dendrometric parameters (total volume, diameter, and height of trunk below the branches) and physical‐mechanical properties (density, total, tangential and radial shrinkage, moisture content, and compression strength) of timber collected from five experimental plots was evaluated. Bark and wood from apricot pruning were then subjected to different extraction techniques, in vitro antioxidant assays, and gas chromatographic studies to determine their antioxidant activity and their phytochemical composition. Bark had the highest antioxidant activity compared to wood. Several antioxidant compounds (e.g., scopoletin and naringenin) were detected in the samples, explaining the measured antioxidant activity. In conclusion, this study demonstrates the potential of using apricot extracts in nutraceutical, cosmeceutical, and industrial fields. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd